Post-irradiation surgery for bronchogenic carcinoma. Issue 4 (July 1969) - Smith, Lawrence; Parnsingha, T.
Abstract : In an attempt to improve both the resectability and survival rates for bronchogenic carcinoma, pre-operative supervoltage radiotherapy was introduced in 1961 and continued for a period of three years. Patients with either a histological or cytological diagnosis were given a tumour dose of 4, 500 r over six weeks and then a two-month period elapsed before surgery. A follow-up of cases treated during the period revealed a five-year survival rate of 15·7%. This rate is low when compared with the results achieved at this hospital with surgery alone. This finding is attributed to the harmful effects of radiotherapy which have led to a high bronchopleural fistula rate of 15·5%. A single case of myocardial radionecrosis also occurred. No improvement is noted in the resectability rate. An overall assessment is that radiotherapy has provided no benefits but has in fact greatly increased both the morbidity and mortality rates.